HYDROCARBON-DEGRADING POTENTIAL OF EXTREMELY HALOPHILIC ARCHAEA IN HYPERSALINE ENVIRONMENTS: A BRIEF REVIEW - Yosmina H. Tapilatu (Pusbindiklat - LIPI, 2012)
The potential of extremely halophilic archaea degrading hydrocarbon in hypersalin environment is reviewed. The emphasis is on the last 30 years studies. The identification of extremely halophilic archaea is important as this type of prokaryote is predominant in the hypersaline environment with NaCl concentration higher than 20% (w/v). Recent studies have shown that extremely halophilic archaea especially those belong to Halobacterium, Haloarcula, and Haloferax might play an important role in hydrocarbon degradation in hypersaline environment. Other that can be found in pristine and hydrocarbon-contaminated hypersaline environment, member of these genuses are also capable of using hydrocarbon as source of energy and carbon.